2018
DOI: 10.1097/ico.0000000000001756
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide Inhibits Neutrophil Recruitment and IL-1β Production in Aspergillus fumigatus Keratitis

Abstract: Purpose:Fungal keratitis is a major cause of corneal ulcers, resulting in significant visual impairment and blindness. Fenretinide, a derivative of vitamin A, has been shown to suppress inflammation in a multitude of diseases. In this study, we aimed to characterize the effect of fenretinide in Aspergillus fumigatus keratitis of the eye in a mouse model.Methods:In vivo and in vitro experiments were performed in mouse models and THP-1 macrophage cell cultures infected with A. fumigatus, respectively. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…IL-1β is an important inflammation mediator and a proinflammatory cytokine (Zhang et al, 2018), which is involved in multiple cellular activities such as cell proliferation, apoptosis, and differentiation (Zhao et al, 2018). IL-33 is a member of the IL-1 family and has been identified as a mediator of various inflammatory diseases such as asthma, cardiovascular diseases, and allergic diseases (Liew et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β is an important inflammation mediator and a proinflammatory cytokine (Zhang et al, 2018), which is involved in multiple cellular activities such as cell proliferation, apoptosis, and differentiation (Zhao et al, 2018). IL-33 is a member of the IL-1 family and has been identified as a mediator of various inflammatory diseases such as asthma, cardiovascular diseases, and allergic diseases (Liew et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…are also involved in fungal keratitis, a major cause of corneal ulcers, resulting in significant visual impairment and blindness. Zhao et al [34] investigated the effect of fenretinide in Aspergillus fumigatus keratitis In vivo in a mouse model as well as In vitro in a THP-1-derived macrophage cell line infected with A. fumigatus. In both experimental models, the pretreatment with fenretinide contributed to protecting corneal transparency during A. fumigatus keratitis in the early phase of the infection by reducing neutrophil recruitment, decreasing myeloperoxidase (MPO) levels and increasing apoptosis.…”
Section: Effectiveness Of Retinoids Against Environmental Humanmentioning
confidence: 99%
“…In both experimental models, the pretreatment with fenretinide contributed to protecting corneal transparency during A. fumigatus keratitis in the early phase of the infection by reducing neutrophil recruitment, decreasing myeloperoxidase (MPO) levels and increasing apoptosis. Compared with controls, fenretinide also impaired proinflammatory cytokine interleukin 1 beta (IL-1β) production in response to A. fumigatus exposure through the blockade of the lectin-type oxidized LDL receptor 1 (LOX-1) and c-Jun N-terminal kinase (JNK) pathway [34]. All retinoids evaluated in Aspergillus spp.…”
Section: Effectiveness Of Retinoids Against Environmental Humanmentioning
confidence: 99%
“…For example, cytokines can be detected at the protein level by ELISA, label-based protein assays, and Western blotting at the RNA level by PCR [32][33][34]36,40,46]. Myeloperoxidase (MPO) is highly abundant in neutrophil granulocytes and other immune cells, and its activity can be measured by commercially available kits; 1 unit of MPO activity corresponds to approximately 2.0 × 10 5 PMNs [36,40,59]. The release of metalloproteases, which mediate the destruction of the corneal extracellular matrix during infection, can easily be assayed by zymography [43].…”
Section: Disease Assessmentmentioning
confidence: 99%
“…This study ultimately indicated that IL-17 expression, but not IFNγ expression, was associated with protective immunity following Aspergillus keratitis [ 58 ]. Zhao et al found that the subconjunctival injection of fenretinide, a synthetic vitamin A derivative that inhibits the activation of NFKβ’s (Nuclear factor kappa-light-chain-enhancer of activated B cells) proinflammatory signaling cascade, resulted in the protection of corneal transparency during an intrastromal model of Aspergillus keratitis utilizing 0.5 × 10 5 conidia/μL [ 59 ].…”
Section: In Vivo Modelsmentioning
confidence: 99%